Avaliação do consumo alimentar e estado nutricional de pacientes com câncer no trato gastrointestinal atendidos em uma unidade hospitalar de referência em Belém-Pa - ABREU, Dandara Carolina Brito de (2023)
Introduction: Malnutrition is a frequent complication in oncologic patients, especially when the neoplasm affects the gastrointestinal tract (GIT). It is known that dietary consumption directly influences the nutritional status and prognosis of cancer patients as well as it is influenced by several factors associated with the disease and its treatment. Purpose: To evaluate the proteinenergy intake and nutritional status of patients with GIT cancer treated at a Hospital Unit in BelémPA. Method: A quantitative, crosssectional, descriptive study with adult and elderly patients with GIT neoplasms under antineoplastic treatment. The 24hour recall was used to evaluate proteinenergy intake, Body Mass Index (BMI), Arm Circumference (AC), Tricipital Skin Fold (TSF), Weight Loss Percentage (WL%) and Subjective Global Assessment Produced by the Patient (ASGPPP) to assess the nutritional status. Results: Of the total of 36 patients, 61.1% were men. The most prevalent tumor site was the stomach (63.9%). A significant percentage of the evaluated patients presented some degree of malnutrition according to BMI (30.6%), CB (65.5%), PCT (86.2%) and ASGPPP (76%). In addition, 77.8% presented significant or severe weight loss. The majority of the patients had energy (77.8%) and protein (58.3%) consumption less than the recommended, even those who were eutrophic and overweight (according to BMI, 80% for energy and 60% for protein). Conclusion: The results showed that the majority of the evaluated patients with GIT cancer presented some degree of malnutrition, besides low energy and protein consumption independent of the nutritional status.